Literatur Review: Stres Kerja, Kompetensi Dan Lingkungan Kerja Terhadap Prestasi Kerja - Siti Fatimah Widya Ningrum (Politeknik Bisnis Indonesia, 2022)
The success of a company could not be separated from the performance of their employees. Of course, this will have an impact on the achievement of company goals. Some aspects of the company that support will make employees improve their performance and even achieve work performance. Employees who succeed in achieving achievements prove that they have given their best work performance. In order to support the creation of outstanding employees, it could not be separated from external and internal factors of employees. In this research, we will find out more about aspects of work stress, competence, and the work environment scientifically. This study aims to produce a conclusion from the phenomena that occur during the research process by collecting various kinds of previous studies. The variables taken in this study are Work Stress, Competence, and Work Environment which can encourage Work Achievement. The research method used in this study is a literature study approach. The results showed that work stress, competence, and work environment can have positive or negative effects and are significant or not significant depending on the object of research.